Performance analysis of double correlated selection combining for cooperative diversity systems - Swaminathan, Ramabadran (2017)
Cooperative diversity is a viable technique to improve the communication reliability and the system throughput. We consider a system comprising of a source (S), a relay (R) and a destination (D). Relay cooperation is achieved through decode and forward protocol. A realistic scenario which considers correlation between SD and RD links is a hardly dealt topic in the literature. Hence, in this paper, a comprehensive effort has been taken to analyse a single-relay cooperative diversity system with selection combining over correlated Nakagami-m fading environment by assuming the correlation between SD and RD links. We derive the end-to-end symbol error probability (SEP) in closed form for M-ary phase shift keying (MPSK) signalling using paired error approach. The analytical results are validated through Monte-Carlo simulations.